Miniseries 2—Septal and paraseptal accessory pathways—Part II: Para-Hisian accessory pathways—so-called anteroseptal pathways revisited. Issue 4 (6th January 2022) - Farré, Jerónimo; Anderson, Robert H; Sánchez-Quintana, Damián; Mori, Shumpei; Rubio, José-Manuel; García-Talavera, Camila; Bansal, Raghav; Lokhandwala, Yash; Cabrera, José-Angel; Wellens, Hein J J; Sternick, Eduardo Back
Abstract: Surgeons, when dividing bypass tracts adjacent to the His bundle, considered them to be 'anteroseptal'. The area was subsequently recognized to be superior and paraseptal, although this description is not entirely accurate anatomically, and conveys little about the potential risk during catheter interventions. We now describe the area as being para-Hisian, and it harbours two types of accessory pathways. The first variant crosses the membranous septum to insert into the muscular ventricular septum without exiting the heart, and hence being truly septal. The second variant inserts distally in the paraseptal components of the supraventricular crest, and consequently is crestal. The site of ventricular insertion determines the electrocardiographic expression of pre-excitation during sinus rhythm, with the two types producing distinct patterns. In both instances, the QRS and the delta wave are positive in leads I, II, and aVF. In crestal pathways, however, the QRS is ≥ 140 ms, and exhibits an rS configuration in V1–2 . The delta wave in V1–2 precedes by 20–50 ms the apparent onset of the QRS in I, II, III, and aVF. In the true septal pathways, the QRS complex occupies ∼120 ms, presenting a QS, W -shaped, morphology in V1–2 . The delta wave has a simultaneous onset in all leads. Our proposed terminology facilitates the understanding of the electrocardiographic manifestations of both types of para-Hisian pathways during pre-excitation and orthodromic tachycardia, and informs on the level of risk during catheter ablation.